2019
DOI: 10.3390/app9153154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Inclined Blade on the Performance of a Sirocco Fan

Abstract: The impeller is the primary working component of centrifugal fans, whose internal flow directly determines the performance of the whole system. This work presents a numerical investigation by using ANSYS-Fluent on the internal flow of a Sirocco fan to investigate the effects of the inclination angle of the blades on the fan performance. The orientation of the blade for the baseline model is strictly along the axial direction, while three inclination angles, i.e., 3.5°, 7.0°, and 10.5°, are chosen for the incli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The characteristics of internal flow in the Sirocco fans were investigated in a number of numerical and experimental works to explore the effect of specific geometric features of the impeller. Ni et al 1 studied the influence of installation angle of V-shaped blades on the aerodynamics performances of a Sirocco fan. The V-shaped blades were designed and installed in parallel with the shaft of the fan.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of internal flow in the Sirocco fans were investigated in a number of numerical and experimental works to explore the effect of specific geometric features of the impeller. Ni et al 1 studied the influence of installation angle of V-shaped blades on the aerodynamics performances of a Sirocco fan. The V-shaped blades were designed and installed in parallel with the shaft of the fan.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have employed steady simulations using two-equation Reynolds-Averaged Navier-Stokes (RANS) turbulence models to investigate centrifugal fan flows or to improve or optimize fan design and performance [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. These publications cover centrifugal fans of different sizes, ranging from flat miniature fans [20,23] to large industrial fans with impeller diameters exceeding one meter [24,28].…”
Section: Introductionmentioning
confidence: 99%
“…The counter-flow in the impeller passage is reduced, and the high pressure area moves to the outlet of the volute. Ni et al 16 discussed the influence of an inclined blade on fan performance, and the results showed that there is an optimal angle, which produces the optimal aerodynamic performance. Engin et al 17 used a ceramic impeller to study the performance characteristics of the impeller and the influence of tip clearance changes on the performance of the fan at high temperature, and found that gas temperature had almost no influence on performance degradation due to tip leakage.…”
Section: Introductionmentioning
confidence: 99%